Deletion of the Candida albicans TLO gene family results in alterations in membrane sterol composition and fluconazole tolerance - Steven Kelly (PLOS ONE, 2024)
Development of resistance and tolerance to antifungal drugs in Candida albicans can compromise treatment of infections caused by this pathogenic yeast species. The uniquely expanded C. albicans TLO gene family is comprised of 14 paralogous genes which encode Med2, a subunit of the multiprotein Mediator complex which is involved in the global control of transcription. This study investigates the acquisition of fluconazole tolerance in a mutant in which the entire TLO gene family has been deleted. This phenotype was reversed to varying degrees upon reintroduction of representative members of the alpha- and beta-TLO clades (i.e. TLO1 and TLO2), but not by TLO11, a gamma-clade representative. Comparative RNA sequencing analysis revealed changes in the expression of genes involved in a range of cellular functions, including ergosterol biosynthesis, mitochondrial function, and redox homeostasis. This was supported by the results of mass spectrometry analysis, which revealed alterations in sterol composition of the mutant cell membrane. Our data suggest that members of the C. albicans TLO gene family are involved in the control of ergosterol biosynthesis and mitochondrial function and may play a role in the responses of C. albicans to azole antifungal agents.